MORPHOLOGICAL COMPARISON OF Octolasmis sp. ECTOPARASITES INFESTING THE GILLS OF SCALLOPED SPINY LOBSTER (Panulirus homarus) WITH DIFFERENT FIXATIVE SOLUTIONS - Yusuf Taufik Hidayat; Kismiyati; Muhamad Amin (Jurnal Biosains Pascasarjana, 2023)
Octolasmis is a type of ectoparasite which is often found on the gills of lobsters. Octolasmis can also be a threat to lobster populations and can even cause high mortality rates. This study aims to detect the effect of different fixative solutions on the morphological characters of Octolasmis infesting the gills of scalloped spiny lobsters (Panulirus homarus). Samples of Octolasmis were collected from the gills of wildly-caught scalloped spiny lobsters in East Lombok, West Nusa Tenggara. The samples were immersed separately in two different fixative solution which are either absolute ethanol or formalin solution. After 7 days, morphological analysis of Octolasmis was analysed using an integrated optilab stereo binocular microscope and a lucida camera. The result showed that there were significant differences in the morphological condition of Octolasmis sp. including skin colour, organ appearance and size of the Octolasmis. In general, the result showed that formalin is better fixative solution.